Who are these Buddhists and How Many of Them are There? Theoretical and Methodological Challenges in Counting Immigrant Buddhists: A Danish Case Study. Issue 1 (2nd January 2016) - Borup, Jørn
Abstract: Religious demography is generally a challenging endeavor and counting and defining religions and religious identities in an Asian context is notoriously difficult. Buddhists in both Asia and the West have a long tradition of gray-zone religiosity, which means that membership and mono-identity is less common than syncretic engagement and hybrid identity. The immigrant Buddhists in the West are generally far more numerous than the convert and new age Buddhists. Their numbers are, however, extremely difficult to ascertain. This article discusses the methodological and theoretical problems in quantifying immigrant religion and the challenges of operationalizing such constraints into concrete methods. The empirical data derive from the author's engagement in research on Buddhism in Denmark, in which traditions from both Theravada and Mahayana groups are represented. While concrete figures are suggested, it is also concluded that further empirical research as well as comparison with more contexts are necessary for the continued refinement of usable methods in counting immigrant religion.